Enhanced thermoelectric properties of Ga-doped In2O3 ceramics via synergistic band gap engineering and phonon suppression1. Issue 17 (7th May 2015) - Liu, Yong; Xu, Wei; Liu, Da-Bo; Yu, Meijuan; Lin, Yuan-Hua; Nan, Ce-Wen
<x xml:space="preserve">Abstract</x> The performance of Ge doped In2O3 thermoelectric materials is enhanced via band structure engineering and phonon suppression.